Effectively reducing the bioavailability of heavy metals in disturbed sediment with biochar: In-situ remediation - Chao Zhang (Elsevier, 2021)
The effect of biochar, derived from Phyllostachys pubescens (PP), on the bioavailability and release fluxes of Cd, Cu, and Zn in disturbed sediments was investigated. The content of Cd, Cu, and Zn in overlying water and pore water sharply increased after sediment disturbance. When biochar dose exceeded 2.96 kg/m2, the maximum amount of Cd, Cu, and Zn in the overlying water was significantly decreased, and a 5 cm biochar layer was formed. Release fluxes of Cd2+, Cu2+, and Zn2+ at the new sediment-water interface were negative diffusion fluxes, which reached maximum values of −0.61, −8.31 and −93.57 μg∙(m2d)−1, respectively. The bioavailability of Cd, Cu, and Zn, measured by diffusive gradients in thin film (DGT) probes, reached 0.92, 5.28 and 34.71 μg∙L−1 in sediment when the biochar dose was 14.78 kg∙m−2, which led to a reduction in [Cd]-DGT, [Cu]-DGT, and [Zn]-DGT by 46.51%, 71.54%, and 61.38%, respectively, compared with blank. Bacterial community analysis showed that low dose treatment(2.96–5.91 kg∙m−2) increased the Chao1 and Shannon of bacterial communities, while high dose treatment (8.87–14.78 kg∙m−2) showed negative effect. Overall, the PP biochar can be used to immobilize heavy metals in disturbed sediments as an economically and feasible method in field.